2015
DOI: 10.1016/j.fertnstert.2015.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Why do array-CGH (ACGH) euploid embryos miscarry? Reanalysis by NGS reveals undetected abnormalities which would have prevented 56% of the miscarriages

Abstract: The objective of this study was twofold; first we wanted to determine the number of blastocysts needed at a certain age to produce at least one euploid blastocyst (>95%) through PGS using whole comprehensive chromosome screening. Secondly, we evaluated the chance of obtaining a euploid embryo in the next cycle after obtaining all aneuploid embryos. DESIGN: Retrospective cohort study. MATERIALS AND METHODS: 10,852 cycles of PGS were performed using blastocyst biopsy and analyzed by array Comparative Genomic Hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In another study, reanalysis by means of hr-NGS of surplus DNA from embryos classified as euploid by means of aCGH that ended up in miscarriage showed that 46% were euploid and the rest mosaic or polyploid (31). Using the same approach, we also found significantly more mosaic embryos in lost pregnancies than in ongoing pregnancies (P¼ .0062) (24).…”
supporting
confidence: 50%
“…In another study, reanalysis by means of hr-NGS of surplus DNA from embryos classified as euploid by means of aCGH that ended up in miscarriage showed that 46% were euploid and the rest mosaic or polyploid (31). Using the same approach, we also found significantly more mosaic embryos in lost pregnancies than in ongoing pregnancies (P¼ .0062) (24).…”
supporting
confidence: 50%
“…In a recent study, blastocyst biopsy specimens from 46 embryos that had miscarried, which had originally been classified as euploid after aCGH, were reanalyzed using HR-NGS. Remarkably, over 50% were shown to be mosaic (4). These data suggest that mosaicism, undetectable by most PGD-A techniques, plays an important role in pregnancy loss.…”
mentioning
confidence: 83%
“…Thus far, the proportion of embryos characterized as euploid using aCGH that can be shown to be mosaic by HR-NGS and additionally go on to produce a term pregnancy is 7% (5), but a larger data set will be needed to determine whether there are differences between mosaics associated with viable pregnancies and those that miscarry. Samples for the HR-NGS studies discussed earlier (4,5) were analyzed by Illumina MiSeq, with manual workflow, and software VeriSeq PGS 1 (Illumina), MCS 2.5, and BFMv4.1.…”
mentioning
confidence: 99%
“…It has been determined that about 30 % of blastocysts are mosaic at the blastocyst stage [25,26]. However, it is important to realize that levels of mosaicism undetectable by current techniques may elevate this statistic and contribute more significantly to pregnancy loss than has been previously understood.…”
Section: Testingmentioning
confidence: 99%